Sabotaged ebook Alaskan courage series, book 5. - Pettrey, Dani (Alaskan Courage, 2015)
Working as search-and-rescue for the Iditarod, Kirra Jacobs and the McKennas race to stop a kidnapper whose threats are more dangerous than they know.